G436(P) Audit and quality improvement of the national health service England (NHSE) specialised service for children with alstrom syndrome. (25th October 2020) - Charalambides, M; Kershaw, M; Pemberton, J; Brock, K; Barrett, T
Abstract : Background: Alstrom syndrome is a rare (1:1, 000, 000) multisystem condition associated with infancy-onset obesity and insulin-resistant diabetes during puberty. It is unknown whether deterioration of renal function begins in childhood and whether this relates to glycaemic control. Primary Aims: To audit children attending the national service (n=24) against the standard of annual BMI, renal, liver function, and glucose control and compare to the 2018 audit. To design BMI-SDS graphs to allow clearer indication of BMI progress. Methods: Case notes and laboratory data were reviewed for 2015–2019. eGFR was calculated using the Counahan-Barratt method. Results: Screening of blood pressure, U&Es and urine albumin creatinine measurements (target level:80%) has improved from 10/24(42%), in the first audit cycle, to 15/22(68%). 11/20(55%) had a reduction in eGFR (median decline 25 ml/min/yr, range:9–58 ml/min/yr) (declining eGFR group) compared to 9/20 (45%) (stable eGFR group). Comparing the declining eGFR to the stable eGFR group, median age was 14.5 yrs (4–17.9 yrs) vs 10.3 yrs (6.5–16.8 yrs); 6/11 (55%) had Hba1c ≥ 6.5%(median 7.3% (5.7–7.7)) vs 9/20(45%); 7/11 (64%) were overweight (≥2 BMI-SDS) vs 6/9 (67%); 4/11 (36%) were obese (>3 BMI-SDS) vs 1/9 (11%); and 8/11(73%) were of South Asian origin vs 3/9 (33%). The average BMI-SDS remained at >2.67SDS (>99.6th centile) in the Asian cohort of Alstrom patients over the 4 years, but decreased from >2.67SDS to 1.5SDS in the White European cohort. Conclusions: Higher BMI-SDS, South Asian origin, older age and poorer glycaemic control were associated with a reduction in eGFR over time. The co-occurrence of these features at puberty may relate to a 'metabolic syndrome' phenotype associated with high levels of insulin resistance known to occur in mid puberty. The results for the South Asian cohort suggest the tendency for the phenotype to remain obese into adulthood. Recommendations: Prospective studies should investigate the drivers to loss of glycaemic control and reduction in eGFR around puberty and the reasons for the ethnic differences in BMI-SDS. Improved monitoring in childhood and earlier pharmacologic and lifestyle interventions may be required to prevent eGFR deterioration and achieve better glycaemic control. Bespoke BMI-SDS charts may empower children and families for weight management. Culturally specific dietetic advice may be helpful.